Factors Affecting Midwives Knowledge About Early Initiation of Breastfeeding at Lut Tawar District Health Center of Central Aceh Regency in 2020 - Barirah Madeni; Hasritawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: Data from the World Health Organization (WHO) shows that there are 170 million children worldwide experiencing malnutrition, 3 million of whom leave each year due to malnutrition. Therefore, WHO recommends, all infants need to receive colostrum (first and second day milk) to fight infection and exclusively breastfed for 6 months to ensure adequate nutrition for infants. This study aims to determine the factors that influence the knowledge of midwives about early initiation of breastfeeding in the working area of the Lut Tawar City Health Center, Central Aceh Regency in 2020. Methods: The research method used is an analytical survey method with a cross sectional approach. The population in this study were all midwives in the area. The city health center serves as many as 59 people. The sampling method uses a total sampling technique that uses all members of the population as a sample. Data collection was carried out on November 15-19, 2020. Results: The results showed that respondents aged > 40 years had good knowledge, namely 64.3%, respondents with DIII education had less knowledge, namely 56.8%, respondents who had never attended breastfeeding initiation training 69.6% respondents who did not often do early initiation of breastfeeding have good knowledge that is 63.9%, respondents who do not get information about early initiation of breastfeeding mostly lack of knowledge that is 58.1%. Conclusion: Factors that influence the knowledge of midwives on early initiation of breastfeeding are education and experience participating in training related to early initiation of breastfeeding.